NURSING CARE FOR GRADE II DIABETIC ULCUS - Margi Rahayu, Umi; Khoirul Huda, Kholis (Journal of Applied Health Management and Technology, 2023)
Background –Uncontrolled diabetes mellitus will cause various complications, one of which is diabetic ulcers. The incidence of diabetic ulcers in DM patients is still high, namely in 2020 it has reached 25% throughout their lives. Patients will be susceptible to severe infections if they do not understand how to properly care for wounds, so that patients with diabetic ulcers can experience problems in the form of impaired tissue integrity. The development of wound care with modern dressing methods has become a trend now, because this wound treatment uses the moist concept so that it speeds up the wound drying process.Objectives –The case study aims to provide nursing care to patients with grade III diabetic ulcers with the main problem being impaired tissue integrity.Method –This type of case study uses a qualitative research design with a case study approach. The sample in this study consisted of 2 diabetic ulcer patients with conventional wound care for 6 days.Results –The results of case management for 6x8 hours showed that the wound condition had decreased in the BJWAT assessment score, but the wound healing process had not been resolved, namely patient 1 on the first day the BJWAT score was 38 then the sixth day it became 28 , while patient 2 on the first day was 39 then days sixth to 27. The wound healing process does take quite a long time, which can reach 12-20 weeks.Conclusion– The conclusion of this scientific paper is that after treating the wound using 0.9% NaCl solution compressed with metronidazole and gentamicin ointment for 6x8 hours, the wound healing process has not been resolved, but the BJWAT wound assessment score has decreased